Práticas com aplicativos móveis para a fixação de conceitos de acústica - Roth, Patrícia Trois (Universidade do Vale do Rio dos Sinos, 2019)
This research studies strategies that can facilitate the implementation of mobile learning in undergraduate academic acoustics activities. It initially addresses the study of the environmental comfort discipline in its historical context, reporting how it was implemented in architecture and urbanism courses and in the environmental context in which we live. In what follows the mobile learning tool is presented as a support for teaching and an explanation of its importance is developed in the current generation. For this dissertation the focus on the tool is through the implementation of mobile applications available on Android and IOS platforms for academic activities in the acoustics discipline and the selection of these. For the finalization of the initial study the concepts commonly approached in the acoustics disciplines are presented. The research method that began with the literature review of the subjects covered, complements with the insertion of a case study, and is defined as follows: the research begins with the literature review of the comfort discipline, the study of the tool of “Mobile learning” and applications, after choosing the discipline “Environmental Comfort III” of the Unisinos Architecture and Urbanism course in order to indicate the content developed for choosing the mobile applications used. A selection of applications is made and thus exercises that introduce mobile laerning in the classroom can be proposed. For the elaboration of the exercises were also used researches in which they were applied and national norms for evaluation and comparison of criteria. At the end of this dissertation, five exercises are proposed that express the knowledge to be developed by students from the beginning to the end of the course with collaborative aspects providing the link between technology and academics.
Keywords: Mobile learning; Conforto ambiental acústico; Exercícios didáticos; Acoustic environmental comfort; Exercises; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo